Upaya Meningkatkan Karakter Wirausaha Anak Usia 5-6 Tahun melalui Bermain Peran Jual Beli di TK Al-Ikhlas Tembung - Lidya Sofiana; Fauziah Nasution; Ahmad Syukri Sitorus (Institut Nalanda, 2025)
This study aims to determine (1) the entrepreneurial character of children aged 5-6 years before carrying out role-playing activities in the form of buying and selling at Al-Ikhlas Tembung Kindergarten (2) The process of role-playing activities in improving entrepreneurial character at Al-Ikhlas Tembung Kindergarten. (3) the entrepreneurial character of children aged 5-6 years after role-playing activities in Al-Ikhlas Tembung Kindergarten. This study was conducted at Al-Ikhlas Tembung Kindergarten, Jln. Bandar Khalifah No. 15 Tembung, Percut Sei Tuan District, Deli Serdang Regency. The research method used Classroom Action Research. While the subjects of this study were 12 children aged 5-6 years. Data collection techniques using observation sheets, interviews and documentation. This study by conducting pre-cycle activities then carried out cycle I and cycle II activities, each cycle was carried out with 2 meetings. Based on the results of the study after being given action I, namely by carrying out role-playing activities in buying and selling, it was obtained from 12 children, there were 7 children in the complete category, and 5 were not complete. So the average value obtained is 18.75%. In cycle II there was a significant increase. Out of 12 children, 10 children were in the completed category and 2 children were in the incomplete category. So the average value obtained was 23.16%.